2007
DOI: 10.1136/bjsm.2007.037978
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of rock-climbing injuries

Abstract: Climbing frequency and technical difficulty are associated with climbing injuries occurring at both indoor and outdoor venues, particularly cumulative trauma to the upper extremities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
128
3
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(151 citation statements)
references
References 18 publications
(28 reference statements)
16
128
3
4
Order By: Relevance
“…Studies that have estimated the reported prevalence of injuries associated with rock climbing vary between 10% and 81% irrespective of cause; between 10% and 50% for impact injuries (9,11,17,37); between 28% and 81% for non-impact acute trauma injuries (9,11,18); and between 33% to 44% for chronic overuse injuries (1,9,37,38). Variance is likely to be 6 associated with differences in the nature, operational level of performance, frequency of performance and duration of activity between climbing disciplines.…”
Section: Prevalence and Incidence Of Injuriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that have estimated the reported prevalence of injuries associated with rock climbing vary between 10% and 81% irrespective of cause; between 10% and 50% for impact injuries (9,11,17,37); between 28% and 81% for non-impact acute trauma injuries (9,11,18); and between 33% to 44% for chronic overuse injuries (1,9,37,38). Variance is likely to be 6 associated with differences in the nature, operational level of performance, frequency of performance and duration of activity between climbing disciplines.…”
Section: Prevalence and Incidence Of Injuriesmentioning
confidence: 99%
“…The most common site of non-impact acute injury and chronic overuse injuries are the upper limbs, particularly the fingers (1,9,38). Diagnosis of finger injuries is challenging due to the complex anatomical structure of fingers and the variability of cause of damage.…”
mentioning
confidence: 99%
“…While alpine climbing has its inherent dangers, sport, indoor and competition climbing showed a minor injury risk [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] . Also, most of the injuries occurring are of minor severity and often due to overuse [1,3,16] .…”
Section: Introductionmentioning
confidence: 99%
“…[6] Retrospective surveys have shed light on the nature and frequency of traumatic injuries sustained while climbing. [37][38][39][40][41][42][43][44][45][46] Advances in cervical spine management and immobilization, opiate-based pain control, and invasive procedures are being discussed. [47][48][49][50][51] Advanced techniques such as shoulder reduction are being taught to lay providers.…”
Section: Traumamentioning
confidence: 99%